Assessing the impacts and feasibility of emissions reduction scenarios in the Po Valley - Colombo, Loris; Marongiu, Alessandro; Malvestiti, Giulia; Fossati, Giuseppe; Angelino, Elisabetta; Lazzarini, Matteo; Gurrieri, Gian Luca; Pillon, Silvia; Lanzani, Guido Giuseppe (Frontiers in Environmental Science, 2023)
This study addresses the crucial goal to improve air quality and meet World Health Organization (WHO) guidelines for pollutant concentrations in Po Valley, one of the hotspots for air pollution in Europe. The research explores the feasibility of emission reduction strategies to achieve near-zero emissions within a limited timeframe, focusing on SOX, NOX, PM, NH3, and NMVOC (non-methane volatile organic compounds) emissions. The study identifies challenges and key observations for various pollutants, emphasizing the need for comprehensive emission reduction strategies. Compliance with interim and WHO levels varies across pollutants and scenarios. Overall, the findings indicate that despite substantial reductions in the emissions (i.e., 80%), recommended levels will not be met in most areas of the Po Valley. Moreover, the research indicates that achieving an 80% reduction solely through technical measures may not be feasible, necessitating drastic reductions in activities to reach emission reduction targets. The study acknowledges that the presented scenarios are theoretical and based on currently available technical elements. It emphasizes that meeting air quality limits requires coordinated efforts and policies at the European Union, national, regional, and local levels. Overall, achieving improved air quality in line with WHO guidelines is a complex process that requires collaborative efforts, policy integration, and further research to assess feasibility and implications.